Government House, Trinidad, B.W.I. - (:unkn) unknown (My University, 2009)
Tropical flora that grow in the garden, line either side of the path that leads to the Government House entrance.
Colour: Sepia; Style: Landscape; Other: Bordered, Undivided
Keywords: Trinidad and Tobago; Postcards; Public buildings--Trinidad and Tobago; Architecture--Trinidad and Tobago; Gardens--Trinidad and Tobago; Historic buildings--Trinidad and Tobago; President's House, The